(untitled) (CAHIERS MAGELLANES-NS, 2024)
This paper compares the conceptual framework of the works of Odia non-dalit and odia dalit writers. The comparison replicates a variety of factors that are associated with the daily existence of Dalits. It concentrates on the contemporary works of odia non-dalit writers that are about Dalits, as Dalit writing is a contemporary phenomenon. The contemporary writers of the upper caste have been examined in order to compare their perspectives on the Dalits with those of the upper caste. It also concentrates on the Odia Dalit writing, which is a recent category and has a recent history. The work of certain Dalit writers has been appropriated. The Manusmriti, which explained the caste laws and bestowed religious sanctity upon them, is the target of the Dalit writings. Their writings are not only a form of reaction against the ascribed identity that is explained in the Hindu scriptures, but also a pursuit of a new identity.